UN RECENTE DEUTERON PROTERON DEL CONSEIL CONSTITUTIONNEL FRA LA LOI DE SÉPARATION DEL 1905 E LA LAÏCITÉ DELLA COSTITUZIONE DEL 1958 (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
The recent Law 1109 of 24th August 2021 also amended the famous 1905 Loi de Séparation.Organisations representing some religious denominations contested these amendments, claiming that the 1905 law would now violate the principle of secularism enshrined in the 1958 Constitution. However, the objection of unconstitutionality is rejected, because the concept of laïcité in the 1958 Constitution is defined precisely by the 1905 law, its historical roots and the doctrinal elaboration of the time that led to its approval.